DYT-TOR1A dystonia: an update on pathogenesis and treatment - Fan, Yuhang; Si, Zhibo; Wang, Linlin; Zhang, Lei (Frontiers in Neuroscience, 2023)
DYT-TOR1A dystonia is a neurological disorder characterized by involuntary muscle contractions and abnormal movements. It is a severe genetic form of dystonia caused by mutations in the TOR1A gene. TorsinA is a member of the AAA+ family of adenosine triphosphatases (ATPases) involved in a variety of cellular functions, including protein folding, lipid metabolism, cytoskeletal organization, and nucleocytoskeletal coupling. Almost all patients with TOR1A-related dystonia harbor the same mutation, an in-frame GAG deletion (ΔGAG) in the last of its 5 exons. This recurrent variant results in the deletion of one of two tandem glutamic acid residues (i.e., E302/303) in a protein named torsinA (torsinA(△E)). Although the mutation is hereditary, not all carriers will develop DYT-TOR1A dystonia, indicating the involvement of other factors in the disease process. The current understanding of the pathophysiology of DYT-TOR1A dystonia involves multiple factors, including abnormal protein folding, signaling between neurons and glial cells, and dysfunction of the protein quality control system. As there are currently no curative treatments for DYT-TOR1A dystonia, progress in research provides insight into its pathogenesis, leading to potential therapeutic and preventative strategies. This review summarizes the latest research advances in the pathogenesis, diagnosis, and treatment of DYT-TOR1A dystonia.